"التمويل الجماعي كآلية مستحدثة لتمويل المؤسسات الناشئة - دراسة تطبيقية في الدول العربية والإسلامية- " - خولة مأمون; باية عبيدي; خولة قرفي (جامعة الوادي University Of Eloued, 2024)
" تهدف هذه الدراسة إلى تسليط الضوء على واقع تطبيق التمويل الجماعي في تمويل المؤسسات الناشئة, وذلك بمعالجة الإشكالية: كيف يمكن أن يساهم التمويل الجماعي كآلية مبتكرة في تمويل المؤسسات الناشئة؟, إذ تم من خلالها التعرف على الإطار النظري للمؤسسات الناشئة ثم الإطار المفاهيمي للتمويل الجماعي, والوقوف على الجانب الواقعي من خلال بعض منصات التمويل الجماعي و أهميتها في تمويل المؤسسات الناشئة فهي تعتبر مكمل لبقية المصادر الأخرى للتمويل,مع الإشارة إلى أنه تم الاعتماد على المنهج الوصفي والتحليلي. إذ أن نتاج الدراسة تمثل في أن التمويل الجماعي يساهم في سد الفجوة التمويلية المتعلقة بالاستثمارات في الشركات الناشئة, والرفع من مستويات تطبيق المشاريع على أرض الواقع بفاعلية وهو الآلية المناسبة لزيادة حظوظ المؤسسات الناشئة, ومن جانب آخر أن هناك العديد من التحديات التي تواجه التمويل الجماعي للمؤسسات الناشئة من بينها الإطار القانوني المنظم لهذا النوع من التمويل, وعليه وجب ضرورة دعم المؤسسات الناشئة لتحقق النجاح المرجو. " " This study aims to shed light on the reality of the application of crowdfunding in financing emerging enterprises, by addressing the problem: How can crowdfunding as an innovative mechanism contribute to financing emerging enterprises? Through it, the theoretical framework of emerging enterprises was identified, then the conceptual framework of crowdfunding. And to look at the realistic side through some crowdfunding platforms and their importance in financing emerging institutions, as they are considered complementary to the rest of the other sources of financing, noting that the descriptive and analytical approach was relied upon. The outcome of the study is that crowdfunding contributes to bridging the financing gap related to investments in emerging companies, and raising the levels of effective implementation of projects on the ground, and it is the appropriate mechanism to increase the chances of emerging institutions. On the other hand, there are many challenges facing crowdfunding for institutions. Emerging institutions include the legal framework regulating this type of financing, and therefore it is necessary to support emerging institutions to achieve the desired success. "
Keywords: مؤسسات ناشئة – تمويل جماعي- منصات تمويل جماعي. Emerging institutions - crowdfunding - crowdfunding platforms